Frequency of Acute Kidney Injury in Infants with Acute Gastroenteritis - Rehman, Sana; Najeeb, Shahzad (Indus Journal of Bioscience Research, 2025)
Background: Acute gastroenteritis is a frequent morbidity during infancy and a serious condition that leads to the complications of acute kidney injury, especially in the context of resource-poor settings. The identification of AKI risk factors in the context is critical in the improvement of outcome. Objective: To determine the frequency of acute kidney injury in children with acute gastroenteritis. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from January to May 2025 at the Department of Pediatric Medicine, MTI-Ayub Teaching Hospital, Abbottabad. Methodology: A total of 285 infants aged 1–12 months with symptoms of acute gastroenteritis were enrolled. Clinical evaluation, laboratory investigations including serum creatinine levels, and demographic data were collected. AKI was defined as serum creatinine ≥50 µmol/L along with clinical signs of renal involvement. Results: The frequency of AKI among enrolled infants was 19.6%. AKI was significantly associated with symptom duration >3 days (p<0.001) and parental employment status (p<0.001). No statistically significant associations were found with age, gender, educational status, social class, residence, or family history of AKI. Conclusion: AKI is a notable complication among infants with acute gastroenteritis.